Does hydropower production influence agriculture industry growth to achieve sustainable development in the EU economies? - Mohd Alsaleh; Abdul Rahim, Abdul Samad (Springer, 2022)
There are many advantages of the hydropower industry, as an environmentally friendly resource, and also some challenges that need to be overcome to fully exploit this sustainable and renewable natural resource. The primary objective of this study is to find out the impact of hydropower factors and economic growth on the agriculture industry output among the EU27 nations within the time factor 1990 to 2021. Adopting the autoregressive distributed lag (ARDL), the findings show a significant positive effect could occur in agriculture industry growth of the European Union (EU13)-emerging economies using hydropower factors than in EU14-emerged economies. On one hand, among additional factors, economic growth and institutional quality contribute more positively to agriculture growth in EU13 economies than in EU14 economies. On the other hand, population density contributes more negatively to agriculture growth in EU13 economies than in EU14 economies. The findings show there can be a positive significant growth increase in the EU13 agriculture industry using fossil fuel output than in EU14 economies. The results show that growth could be sustained in the agricultural industry of the European nations by increasing the level of hydropower production as this will help in attaining sustainable development by the year 2030. This will therefore help in mitigating the effect of climatic changes due to environmental pollution. The projected calculations were seen to be reliable and valid and this was attested to by the three estimators used in the study (pooled mean group, mean group, and dynamic fixed effect). This study recommended that European nations could leverage hydroelectricity to achieve sustainable growth and development. The legislative arms of the government of these European nations should as well show more interest in green energy to achieve security and sustainable development in hydroelectricity production. Decision-makers in the EU nations should buttress more emphasis on sustainable means through which hydropower could be used to attain sustainable irrigation systems for the agriculture industry and thus minimize the demand for fossil fuels and reduce CO2-related emissions in the future tine ahead.